Holistic Management of A Female Patient with Diabetic Neuropathy and Osteoarthritis through Family Medicine Approach - Marcella Dena Fernanda; Diana Mayasari (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2025)
Diabetic neuropathy is the most common complication found in diabetes patients, with a lifetime prevalence of over 50% among those with diabetes. The World Health Organization (WHO) estimates that approximately 528 million people worldwide suffer from osteoarthritis (OA), an increase of 113% since 1990. The progression of diabetic neuropathy can be controlled through a healthy lifestyle and medication adherence, as can osteoarthritis through healthy living and physical exercise. This study applies family doctor services by identifying internal and external risk factors, clinical problems, and patient management based on Evidence-Based Medicine, focusing on the patient, family, and community. This study is a case report that collects primary data through anamnesis, physical examination, home visits, and environmental data, along with secondary data from the patient’s medical records. Assessments were conducted holistically, both qualitatively and quantitatively, from the beginning to the end of the study. Mrs. Y, 61 years old, presented with complaints of numbness and tingling in all four limbs accompanied by pain in both knees, with a history of diabetes for 15 years. The patient was diagnosed with diabetic neuropathy and osteoarthritis. In this case, diagnosis and management were carried out according to relevant theories and journals. Following intervention, there was a reduction in clinical symptoms and an increase in knowledge among the patient and her family. The diagnosis and management of this patient were conducted holistically, patient-centered, with a family approach, and community-oriented. Based on several current theories and studies, there was an improvement in the patient’s family knowledge.